Conjugate Analysis of Heat-Species-Charge Transport for Evaluating Effects of the Temperature Gradient on Cell Performance. (14th September 2015) - Miyagawa, Kiyofumi; Araki, Takuto
Abstract : Understanding the water transport phenomena in the Proton Exchange Membrane Full Cell (PEMFC) is very important to estimate the cell performance. However, temperature, electrochemical reaction and liquid water, active materials and heat transports have been interacted each other. So, the conjugate analysis considering all of them spontaneously is required. In particular, the temperature gradient has the significant influence on water transport. Then, the two-dimensional unsteady model considering distributions of temperature, spices and reaction in components of the PEMFC was developed to investigate how the temperature gradient effects on the water transport and the cell performance. The result indicated the temperature gradient invoke heat pipe phenomena. As the result, the temperature gradient promoted liquid water drainage in PEMFC. Finally, it was proved that considering the temperature gradient impacted the water transport and the cell performance, and the temperature gradient was necessary.